ANALISIS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS DI SMPN 4 TAROGONG KIDUL (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Make a Match type cooperative learning model in improving students’ learning motivation in Social Studies (IPS) at SMP Negeri 4 Tarogong Kidul. This research employed a qualitative method with a field research approach. The subjects of this study were students and a Social Studies teacher selected purposively. Data were collected through observation, interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, with data validity ensured through triangulation. The results showed that before the implementation of the Make a Match model, the learning process was dominated by the lecture method, which made students passive and less motivated. After the implementation, there was a significant improvement in students’ activeness and learning motivation. Students became more enthusiastic, actively participated, and showed greater confidence in asking questions and expressing opinions. In addition, the learning atmosphere became more interactive and enjoyable, which helped students understand the material better. In conclusion, the Make a Match cooperative learning model is effective in improving students’ learning motivation in Social Studies. This model can be used as an alternative innovative teaching strategy to create an active, creative, and enjoyable learning environment.